Beyond scarcity and its management: Sociocultural dimensions of the water crisis in the Atacama Desert. Issue 7 (28th June 2022) - Cantillana, Raphael; Iniesta-Arandia, Irene
Abstract: The depletion of freshwater sources by indiscriminate industrial actions is one of the direct causes of the current water crisis. One of the emblematic cases of this problem is the Atacama Desert, a unique hyper-arid zone in which an extensive copper industry depletes its scarce freshwater reserves. This territory, occupied for millennia by indigenous groups, is experiencing a water crisis that threatens its very subsistence. This paper uses the ethnographic method and the Water Justice framework to approach the everyday and often invisible issues of this crisis within the Mamiña community. This Quechua community holds an ambivalent position in front of the copper mine project because of its control of the water rights, the economic interests of some of their members, and the role of the Aymara minority. We suggest that researchers in this field pay more attention to the communities' internal diversity and its relations with the copper industry to understand how the water crisis is detached from its biophysical conceptions to be socioculturally constructed. HIGHLIGHTS: The water crisis in the Atacama Desert is not only related to its natural conditions of biophysical scarcity. An investigative approach focused on the sociocultural dimension could better show the everyday interactions of current water problems. The interweaving of sociocultural practices and discourses with the conditions of the environment are key cornerstones to understanding how the water crisis is constructed. The hyper-arid conditions of the desert and the scarce information on indicators hide the environmental damage that occurs in it. Graphical Abstract